The Biology of IgG Subclasses and Their Clinical Relevance to Transplantation. (January 2018) - Valenzuela, Nicole M.; Schaub, Stefan
Abstract : Abstract: Immunoglobulin G (IgG) is the dominant immunoglobulin and can be divided into 4 distinct subclasses. The evolution of IgG subclass switches is regulated by interaction with T cells and follows a 1-way direction (IgG3 → IgG1 → IgG2 → IgG4). Based on their structure, the 4 IgG subclasses can initiate different effector function such as complement activation, recruitment of various cells by Fc receptors, and agonistic signaling. Using current assays for HLA antibody detection as a template and replacing the generic reporter antibody with IgG subclass–specific reporter antibodies, it is possible to investigate the IgG subclasses of HLA antibodies. There are 15 different IgG subclass compositions possible. Based on the capability to activate the complement system and the class switch direction, 3 arbitrary patterns can be defined (ie, only complement-binding subclasses [IgG3 and/or IgG1], expansion to noncomplement-binding subclasses [IgG3 and/or IgG1 plus IgG2 and/or IgG4], and switch to noncomplement-binding subclasses [IgG2 and/or IgG4]). The latter group accounts for less than 5%, whereas the former 2 groups have a similar prevalence close to 50%. In the past 5 years, several studies correlated the IgG subclass pattern with occurrence of antibody-mediated rejection and allograft outcomes. Because of differences of the used IgG subclass assay, the time point of analyses, and the definition of outcomes, a clear picture has not emerged yet. Future needs are standardization of the assay, a more detailed knowledge of the initiated effector functions, and more well-designed clinical studies also looking at changes of the IgG subclass pattern over time.